Anti-Rheumatoid Arthritic Effects of Paris Saponin VII in Human Rheumatoid Arthritis Fibroblast-Like Synoviocytes and Adjuvant-Induced Arthritis in Rats - Meng, Mei; Yue, Zhenggang; Chang, Lu; Liu, Yanru; Hu, Jinhang; Song, Zhongxing; Tang, Zhishu; Zhou, Rui; Wang, Changli (Frontiers in Pharmacology, 2021)
In the pathogenesis of rheumatoid arthritis (RA), rheumatoid arthritis fibroblast-like synoviocytes (RA-FLS) have tumor-like characteristics, mainly manifested by hyperproliferation and resistance to apoptosis, and then it will erode the bone and cartilage, eventually leading to joint destruction. Paris saponin VII (PS VII) is an active compound derived from a traditional herbal medicine named Trillium tschonoskii Maxim., which has anti-tumor, analgesic and immunomodulatory effects. However, its anti-RA effect has not yet been reported. This study was to investigate the effect of PS VII on two rheumatoid arthritis fibroblast-like synoviocytes lines (RA-FLS and MH7A) and adjuvant-induced arthritis (AIA) in rats. In vitro, the effects of PS VII on the proliferation, cell cycle and apoptosis of RA-FLS and MH7A cells were detected by MTT, flow cytometry, and western blot analysis. In vivo, the effect of PS VII on the weight of the rat, paw swelling, ankle joint diameter, arthritis index, serum inflammatory cytokines (TNF-α, IL-6, and IL-1β), histopathological assessment and apoptosis proteins in the synovial tissues were evaluated in AIA rats. The in vitro studies showed that PS VII inhibited the proliferation of RA-FLS and MH7A cells, induced S phase arrest and triggered cell apoptosis mainly through the mitochondrial apoptotic pathway and the regulation of JNK and p38 MAPK pathways. The in vivo studies revealed that PS VII could improve ameliorate body weight, paw swelling, ankle joint diameter, reduce the spleen and thymus index, suppress the production of TNF-α, IL-6 and IL-1β, improve histopathological changes and regulate the expressions of apoptosis proteins in AIA Rats. In conclusion, PS VII could inhibit the proliferation and trigger apoptosis of RA-FLS and MH7A cells by regulating the mitochondrial apoptosis pathway and the JNK and p38 MAPK pathways, and alleviate the symptoms of RA, signifying it to be one of the potential anti-RA therapeutics.